2007
DOI: 10.1111/j.1750-3841.2007.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grape Seed Extract on Physicochemical Properties of Ground, Salted, Chicken Thigh Meat during Refrigerated Storage at Different Relative Humidity Levels

Abstract: The effect of grape seed extract (GSE, 0.1%) +/- NaCl (1%) in ground chicken thigh meat during refrigerated storage at 59%, 76%, 88%, and 99% relative humidity (RH) was examined. Compared to the untreated control, GSE (0.1%) delayed the reduction of water activity (a(w)) that occurred during refrigerated storage at different relative humidity levels but had no effect on moisture content or pH compared to the untreated control. GSE inhibited the formation of a secondary marker of lipid oxidation (TBARS) compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 27 publications
7
55
0
7
Order By: Relevance
“…The lowest TBARS values were in the sample containing 10 % GSP, indicating that GSP effectively retards lipid oxidation during frozen storage and can be used as an alternative to commercial antioxidants. Similarly, Brannan (2008) reported an increase in the TBARS values of chicken meat during refrigerated storage. The ability of grape seed to inhibit lipid oxidation is likely related to its rich polyphenol content, especially proanthocyanidin.…”
Section: Changes In Povs During Frozen Storage Of Precooked Chicken Nmentioning
confidence: 83%
“…The lowest TBARS values were in the sample containing 10 % GSP, indicating that GSP effectively retards lipid oxidation during frozen storage and can be used as an alternative to commercial antioxidants. Similarly, Brannan (2008) reported an increase in the TBARS values of chicken meat during refrigerated storage. The ability of grape seed to inhibit lipid oxidation is likely related to its rich polyphenol content, especially proanthocyanidin.…”
Section: Changes In Povs During Frozen Storage Of Precooked Chicken Nmentioning
confidence: 83%
“…Brannan (2008) found that grape seed extract helps to mitigate the prooxidative effects of NaCl in stored ground chicken without affecting moisture content or pH. The author suggests that grapeseed extract may alter the effect of NaCl on protein solubility in salted chicken patties.…”
Section: Effects Of the Food Matrix And Ingredientsmentioning
confidence: 99%
“…Hence there is a growing interest in natural antioxidants in meat products. Many research reports demonstrated antioxidant effects of grape seed extracts in poultry meat (Brannan 2008), tea catechins in chicken patties (Mitsumoto et al 2005), rosemary and sage in chicken nuggets (O'Sullivan et al 2004) and extracts of pomegranate and kinnow peels in chicken meat products (Devatkal et al 2011).…”
Section: Introductionmentioning
confidence: 99%